Fecal metabolite of a gnotobiotic mouse transplanted with gut microbiota from a patient with Alzheimer's disease. Issue 11 (2nd November 2019) - Fujii, Yusuke; Nguyen, Thuy Tien Thi; Fujimura, Yuta; Kameya, Naotaka; Nakamura, Shoji; Arakawa, Kensuke; Morita, Hidetoshi
ABSTRACT: Studies of Alzheimer's disease are based on model mice that have been altered by transgenesis and other techniques to elicit pathogenesis. However, changes in the gut microbiota were recently suggested to diminish cognitive function in patients, as well as in model mice. Accordingly, we have created model mice of the human gut microbiota by transplanting germ-free C57BL/6N mice with fecal samples from a healthy volunteer and from an affected patient. These humanized mice were stably colonized and reproduced the bacterial diversity in donors. Remarkably, performance on Object Location Test and Object Recognition Test was significantly reduced in the latter than in the former at 55 weeks of age, suggesting that gut microbiota transplanted from an affected patient affects mouse behavior. In addition, metabolites related to the nervous system, including γ-aminobutyrate, taurine, and valine, were significantly less abundant in the feces of mice transplanted with microbiota from the affected patient. Graphical abstract: : Transplantation of fecal microbiota from patients with Alzheimer's disease alters fecal metabolome and behavior in recipient mice.